Reconstructing Islamic Jurisprudence in Local Marriage Practices: A Legal-Ethnographic Study of Jujuran in Banjar Society - Hayati, Fauziah; Seff, Nadiyah; Hafidzi, Anwar (El-Qist: Journal of Islamic Economics and Business (JIEB), 2025)
This study aims to investigate the practice of jujuran—a traditional monetary gift in Banjar marriage customs—from the perspective of Islamic jurisprudence and legal anthropology. Through a juridical-normative and legal-ethnographic approach, the research reveals that jujuran functions not as commodification of women, but as a culturally embedded expression of honor, responsibility, and economic solidarity. Drawing on principles such as maṣlaḥah (public interest), ‘urf (custom), and the objectives of Islamic law (maqāṣid al-sharī‘ah), the study reinterprets jujuran as a legitimate and dynamic legal norm that contributes to wealth redistribution, gender equity, and the preservation of marital dignity. The findings highlight that Banjar women actively participate in jujuran negotiations, challenging patriarchal interpretations and revealing women’s agency within customary frameworks. This research advances the discourse on contextual Islamic legal theory (fiqh al-‘urf) by demonstrating how local traditions, when aligned with Islamic ethical values, can serve as instruments for inclusive and justice-oriented marital practices. It contributes to global Islamic legal scholarship by offering a model for harmonizing cultural heritage with contemporary legal reform. Future research should explore comparative studies across Muslim ethnic groups and examine the evolving role of technology and digital mediation in customary marriage practices.